Exploring the Difficulties in Writing Skills among Students at Vocational High School No. 1 Sukasada - Aritona, Gede; Mahayanti, Ni Wayan Surya; Adnyayanti, Ni Luh Putu Era (PEMA, 2025)
This study explores the writing challenges faced by grade 11 hospitality students at SMKN 1. Sukasada, Bali. Using a qualitative descriptive approach, data was collected through a questionnaire from 13 students, which featured both closed and open-ended questions. The findings revealed significant obstacles such as inadequate practice in writing, preference for theoretical learning over practical application, and heavy reliance on translation tools. Students had difficulties with grammar, mechanical errors and limited vocabulary, which affected their proficiency in English communication. This study underscores the importance of integrating practical writing exercises with theoretical instruction to improve language skills and reduce reliance on translation aids. It advocates educational strategies that emphasize regular writing practice and balanced assessment to better prepare students for success in the hospitality industry.